2022
DOI: 10.1038/s41598-022-21234-z
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric sensor arrays for the differentiation of baijiu based on amino-acid-modified gold nanoparticles

Abstract: It is of great significance for quality control to realize the discrimination for baijiu from different brands and origins. Strong-aroma-type baijiu (SAB), one of the most important Chinese aroma-type baijiu, exhibits the largest variety and market share. In this study, we proposed colorimetric sensor arrays based on gold nanoparticles (AuNPs) modified with different amino acids (AAs) to recognize the organic acids, and further distinguish different SABs. Three representative AAs, namely methionine (Met), tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Three representative amino acids, namely methionine (Met), tryptophan (Trp) and histidine (His), were utilised for the modification of gold nanotubes as reported by Jia et al [205] for the detection of distinctive organic acids found in the aromatic liquor Chinese baijiu.…”
Section: Colourimetric Sensorsmentioning
confidence: 99%
“…Three representative amino acids, namely methionine (Met), tryptophan (Trp) and histidine (His), were utilised for the modification of gold nanotubes as reported by Jia et al [205] for the detection of distinctive organic acids found in the aromatic liquor Chinese baijiu.…”
Section: Colourimetric Sensorsmentioning
confidence: 99%
“…Some applications require complex receptors that cannot transmit optical signals and need additional colorants. The employed receptors encompass small molecules, 200 amino acids, 201 polymers, 202,203 DNA, 204,205 or peptides, 20 each with its unique set of advantages and limitations. The selection among these receptors depends on the specific application requirements and their compatibility with the desired transducer.…”
Section: Sensor-array Designmentioning
confidence: 99%